2019
DOI: 10.17344/acsi.2018.4723
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus as Antifungal Agent

Abstract: Tacrolimus (FK506) is an immunosuppressant drug widely used to avoid organ rejection in transplant patients. It has a profound influence on the cellular stress response by interfering with the calmodulin-calcineurin signaling pathway. In this context FK506 also became a valuable antifungal drug in medical care. Here it is shown in vitro that tacrolimus has a potent growth inhibition activity against 11 fungi and 3 oomycetes of agricultural importance. The significance of this finding is discussed with respect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Disulfiram, a drug inhibiting the aldehyde dehydrogenase (P05091) that is used to treat chronic alcoholism, showed strong inhibitory effects in Candida albicans and Candida auris [ 30 ]. The immunosuppressive drug tacrolimus, targeting the peptidyl-prolyl cis-trans isomerase FKBP1A (P62942) had effects in 11 fungi and 3 oomycetes of agricultural importance [ 31 ]. Finally, vorinostat, targeting histone deacetylases (Q92769, Q9UBN7) and used in the treatment of cutaneous T cell lymphomas, showed strong effects in Aspergillus spp.…”
Section: Resultsmentioning
confidence: 99%
“…Disulfiram, a drug inhibiting the aldehyde dehydrogenase (P05091) that is used to treat chronic alcoholism, showed strong inhibitory effects in Candida albicans and Candida auris [ 30 ]. The immunosuppressive drug tacrolimus, targeting the peptidyl-prolyl cis-trans isomerase FKBP1A (P62942) had effects in 11 fungi and 3 oomycetes of agricultural importance [ 31 ]. Finally, vorinostat, targeting histone deacetylases (Q92769, Q9UBN7) and used in the treatment of cutaneous T cell lymphomas, showed strong effects in Aspergillus spp.…”
Section: Resultsmentioning
confidence: 99%
“…The antitumor, antimicrobial, and fungicidal activity of S-substituted tetrazolo[1,5-c]quinazoline-5(6Н)-thiones were described by Antypenko et al 52,53 It was shown, that 2-(tetrazolo[1,5-с]quinazolin-5-ylsulfanyl)ethanones 100c-g ( Fig. 1) Compounds 100c-g revealed moderate antitumor activity against standard NCI lines panel (Fig.…”
Section: Biological Properties Of 2-thiopyrimidinesmentioning
confidence: 92%
“…The subsequent alkaline hydrolysis of compound 50 allowed to obtain 1,5-binucleophile 51 which was then transformed into ribosylpyrophosphate 2-mercapto-1,N 6 -ethenoadenosine diphosphate (52) via [5+1] heterocyclization with carbon disulfide. Alkylation of compound 52 by 3-bromopropanamine yielded the corresponding 2-[(3-aminopropyl)sulfanyl]-1,N 6 -ethenoadenosine diphosphate (53). Further degradation of the imidazole cycle by N-bromosuccinimide allowed to obtain 2-[(3-aminopropyl)sulfanyl]adenosine diphosphate (54).…”
Section: [5+1] Heterocyclizationmentioning
confidence: 99%
“…Recently, the potent in vitro antifungal activity of tacrolimus (FK 506 Fujimycin; Figure 1 ) toward fungi and oomycetes was demonstrated [ 28 ]. Tacrolimus is a macrolide lactone isolated and characterized from Streptomyces tsukubaensis [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some components of the calcium-calcineurin signaling pathway vital for fungal growth have been identified as potential and effective targets for the development of new therapeutic drugs [ 31 , 32 ]. Tacrolimus has not been analyzed in the context of plant protection in agriculture thus far, beyond our own study [ 28 ], and it is not found in the “Pesticide Properties DataBase” [ 33 ].…”
Section: Introductionmentioning
confidence: 99%